Global convergence in leaf respiration from estimates of thermal acclimation across time and space. Issue 4 (21st April 2015) - Vanderwel, Mark C.; Slot, Martijn; Lichstein, Jeremy W.; Reich, Peter B.; Kattge, Jens; Atkin, Owen K.; Bloomfield, Keith J.; Tjoelker, Mark G.; Kitajima, Kaoru
Summary: Recent compilations of experimental and observational data have documented global temperature‐dependent patterns of variation in leaf dark respiration ( R ), but it remains unclear whether local adjustments in respiration over time (through thermal acclimation) are consistent with the patterns in R found across geographical temperature gradients. We integrated results from two global empirical syntheses into a simple temperature‐dependent respiration framework to compare the measured effects of respiration acclimation‐over‐time and variation‐across‐space to one another, and to a null model in which acclimation is ignored. Using these models, we projected the influence of thermal acclimation on: seasonal variation in R ; spatial variation in mean annual R across a global temperature gradient; and future increases in R under climate change. The measured strength of acclimation‐over‐time produces differences in annual R across spatial temperature gradients that agree well with global variation‐across‐space. Our models further project that acclimation effects could potentially halve increases in R (compared with the null model) as the climate warms over the 21st Century. Convergence in global temperature‐dependent patterns of R indicates that physiological adjustments arising from thermal acclimation are capable of explaining observed variation in leaf respiration at ambient growth temperatures across the globe.